Afrocucumis africana (Semper, 1867) (Holothuroidea: Dendrochirotida:Cladolabidae), new addition to the holothuroid fauna of Pakistan - Shaikh, Iqra; Ali, Qadeer Mohammad; Thandar, Ahmed; Ahmed, Quratulan (Zootaxa, 2023)
Two dendrochirotid holothuroids, here identified as Afrocucumis africana, were collected from Gariyan Beach, Jiwani Makran Coast, Balochistan, for morphological and taxonomic study. This species is a new record of a dendrochirotid holothuroid from the Pakistani coastal waters. Identification was confirmed through morphology and microscopic observations of the ossicles. Identified specimens are deposited in Marine Reference Collection and Resource Centre, University of Karachi.